FAKTOR-FAKTOR YANG MEMPENGARUHI MIGRASI INTERNASIONAL DI PROPINSI JAWA TIMUR - Novitasari, Ria (Jurnal Ilmiah Mahasiswa FEB, 2016)
Factors affecting International Migration in East Java. The study also identifies the factors affecting international migration in East Java. This study was a quantitative research. By using multiple regression analysis using the data Podes (Village Potential revenue) in 2014. The results showed a number of factors affecting international migration in East Java province, educational institutions (X1), industrial (X2), market (X3), cooperatives ( X4) and rural incomes (X6). While credit facility (X5) does not affect international migration. The government has provided various credit facilities areas such as business credit (KUR), credit food and energy (KKP-E) and small business loans (KUK), but not enough to prevent international migration due to economic factors that increase their wages are higher wages non-migrant population.Keywords: International Migration, Institute of Education, Industry, Markets, Cooperatives, Credit Facility and Rural incomes.